Valorisation of dragon fruit peel in drinking yoghurt: Development, physicochemical, proximate, functional properties, and shelf-life evaluation - Maryam Saeed Hafiz; Karunanayaka Mudiyanselage Imayuru Ushada Karunanayaka; Kartika Nugraheni; Ganwarige Sumali Nivanthi Fernando (Czech Journal of Food Sciences, 2025)
Dragon fruit peel (Hylocereus spp.), often discarded as waste has gained interest for its anti-aging, anti-inflammatory, and anti-diabetic properties. Peels make up to 22-44% (w.w-1) of the fruit's weight and this waste could make a significant effect on the environment. Therefore, this study aimed to develop a drinking yoghurt using dragon fruit peel extract as a natural colorant and evaluate its physicochemical, proximate, functional, and shelf-life properties. The sugar concentrations (4, 6, and 8% w.w-1) and incubation times (4, 6, and 8 h) were changed to optimise the product. Sensory evaluation by 30 semi-trained panellists using a 5-point hedonic scale identified 6% (w.w-1) sugar and an 8 h incubation as optimal. Compared to plain drinking yoghurt, the dragon fruit peel (DFP) drinking yoghurt showed higher crude fat (2.87%), fibre (0.72%), ash (0.66%), moisture (84.08%), total antioxidants (824.3 mg TE.100 g-1), flavonoids (0.22 mg QE-1.mL-1), and betalains content (0.0064 mg.mL-1). During storage, DFP yoghurt's pH declined, with minimal betalain loss, and it remained stable for three weeks at 4 °C without preservatives. This study demonstrates the potential of dragon fruit peel as a functional ingredient in yoghurt, offering nutritional and environmental benefits.